ダイ18ジ ナンキョク チイキ カンソク エットウタイ ホウコク 1977-1978 - 楠, 宏; クスノキ, コウ; KUSUNOKI, Kou (国立極地研究所, 1979)
P(論文) 18次越冬隊員30名は,1977年2月1日から1年間,昭和基地とみずほ基地において,国際磁気圏観測に関係した観測を重点的に行った.昭和基地では極光,地磁気,電離層,気象,地震,潮汐の定常観測が行われたほか,ロケット6機の打ち上げ,人工衛星信号受信,大気球観測などの超高層部門の重点観測があり,気象・地理・医学・生物の研究も行われた.みずほ基地および新設の無人観測点A1 (69°47'S, 41°35'E)でも超高層部門の多点観測を行った.みずほ基地は前年に引き続き維持され,通年4名が超高層のほか,雪氷,地上気象の観測を行った. Thirty men of the wintering party occupied Syowa Station and Mizuho Station from February 1, 1977 to January 31, 1978, carrying out observations in many scientific disciplines, particularly laying emphasis on the upper atmosphere physics in connection with research programs of the International Magnetospheric Study (IMS). At Syowa Station, in addition to the observations of aurora, geomagnetism, ionosphere, meteorology, seismology, marine geomorphology, ocean tide, biology, and medical science, the major research program covers the launching of 6 sounding rockets, reception of data signals from scientific observation satellites, and launching of large balloons to carry out the IMS project. Mizuho Station was continuously occupied by 4 men in rotation so as to carry out observations of upper atmosphere physics, glaciology, and meteorology. An unmanned geophysical observation station "AI" was established at 69°47'S and 41°35'E in January 1977, and the record of geomagnetism, ionospheric absorption, and elimatological elements was obtained. departmental bulletin paper